Labelling for Good: A Descriptive Study of Nutritional Label Format and Design to Help Consumers Make Better-Informed Choices - Koh, Pouline Chai Lin; Abd Rahman, Zainurul Aniza (Universiti Sains Malaysia, 2014)
Nutritional labels are commonly used on food packaging in Malaysia, but currently the standard format of nutritional label design in Malaysia are not defined to help better inform the consumers. The lack of format determinants used by manufacturers was barely discussed. A very small number of studies were done in the area of information design in Malaysia on the consistencies in the format of nutritional label. This paper aims to explore the aesthetic value and design attention as the prime commodities of a nutritional label to meaningfully convey about what is consumed to keep the consumers better informed. This paper will look at the nutritional label format and design on packaged food available in the Malaysian hypermarkets, and provide discussion of the new insights for better visual representation through information design. It will draw on the descriptive studies of nutritional label format and design that encompasses the existing format used on imported and local packaged food, which can be found in Malaysian hypermarkets. The findings will be supported and addressed with qualitative approach to provide rich information.